2015
DOI: 10.1371/journal.pone.0143755
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Profiling Implies New Markers of Gemcitabine Chemoresistance in Mutant p53 Pancreatic Ductal Adenocarcinoma

Abstract: BackgroundNo reliable predictors of susceptibility to gemcitabine chemotherapy exist in pancreatic ductal adenocarcinoma (PDAC). MicroRNAs (miR) are epigenetic gene regulators with tumorsuppressive or oncogenic roles in various carcinomas. This study assesses chemoresistant PDAC for its specific miR expression pattern.MethodsGemcitabine-resistant variants of two mutant p53 human PDAC cell lines were established. Survival rates were analyzed by cytotoxicity and apoptosis assays. Expression of 1733 human miRs wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 60 publications
3
47
1
Order By: Relevance
“…Several studies of other tumor types have demonstrated the importance of TP53 and chemotherapy efficacy: functional TP53 is necessary for effective apoptosis in response to cytotoxic agents. Conversely, the loss of TP53 function limits efficacy and enhances resistance to conventional cytotoxic chemotherapy, and it has been implicated in gemcitabine and platinum resistance in other malignancies …”
Section: Discussionmentioning
confidence: 99%
“…Several studies of other tumor types have demonstrated the importance of TP53 and chemotherapy efficacy: functional TP53 is necessary for effective apoptosis in response to cytotoxic agents. Conversely, the loss of TP53 function limits efficacy and enhances resistance to conventional cytotoxic chemotherapy, and it has been implicated in gemcitabine and platinum resistance in other malignancies …”
Section: Discussionmentioning
confidence: 99%
“…Both miR-99a and miR-491 may play different roles in various cancers as they regulated different target genes. The miR-99a has been reported to regulate resistance in breast cancer 18, leukemia 19, neck squamous cell carcinoma 20, germ cell tumor 21, pancreatic ductal adenocarcinoma 22, cholangiocarcinoma23, etc. The relation between miR-491 and liver cancer 24, colorectal cancer 25, ovarian carcinoma 26, pancreatic cancer 27, oral squamous cell carcinoma 28, non-small cell lung cancer 29, etc has also been verified.…”
Section: Discussionmentioning
confidence: 99%
“…In essence, over 10% of all reported research findings of miRNA influences in cancer chemoresistance demonstrated that such a phenotype modulation was effected through simultaneous dysregulation of multiple miRNAs, rather than an individual putative chemoresistance miRNA—though no specific miRNA combination was identified as most prevalent by the authors [44,46,47,48,49,62,67,71,76,81,85,88,132,133,158,168,201,203,211,212,213,217,223,224,228,230]. This suggests that miRNA influences on cellular functions also occur at a more complex level, whereby it is a signature dysregulated expression pattern of two (or more) miRNAs that trigger simultaneous downregulation of a specific set of target transcripts leading to an ultimate change in cellular/tissue phenotype.…”
Section: Influences Of Mirnas In Cancer Chemoresistancementioning
confidence: 99%